The Secret Reasons for the Western Scholars Studies The Biography of the prophet - جاسم صكبان علي (College of Education for Women, 2019)
Western Scholars have criticized al the material on the point of reliability . Some have taken the unduly Sceptical view that nothing is to be trusted except Quran . The present study is based on opposing view that at least the material in the early biographers is to be accepted as true , except where there are particular reasons for thinking that an anecdote has been distorted ( or invented ) through legal or political motives. It is also assumed that most of the background material culled from a large number of vaired works , is sound . This standpoint .I would claim , leads to a coherent view of Muhammad's life and achievement.